Designing an electricity tax system in presence of international regulations and multiple public goals: An empirical assessment - Geir H. Bjertnæs; Taran Fæhn; Jørgen Aasness (Statistics Norway, Research Department, 2008)
The European competition rules restrict governments' opportunity to differentiate terms of energy accessibility among firms and industries. This easily runs counter with regional and industrial goals of national energy policies. Norway levies a tax on use of electricity, but exempts main industrial usages. This analysis assesses alternative, internationally legal, designs of the system in terms of their effects on efficiency and distribution, including industrial objectives. Among the reforms we explore, removing the exemptions would be the most effective way of raising revenue, but it would be politically costly by deteriorating the competitiveness of today's favoured industries. An entire abolishment of the electricity tax, and replacing revenue by increased VAT, would generate a more equal distribution of standard of living and, at the same time, avoid the trade-off between efficiency and competitiveness.
Keywords: D31; D58; F15; H21; H23; J68; L52; 330; Tax reform; Multiple policy goals; Computable general equilibrium model